Implementation of the Independent Curriculum in History Education at State Senior High Schools 1 Purbolinggo - Miftakhudin, Arif; Hartati, Umi; Afwan, Bahtiar; Sartika, Lianda Dewi (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The aim of this research is to analyze the implementation of the Independent Curriculum (Merdeka) in history learning at State Senior High Schools (SMA Negeri) 1 Purbolinggo. The type of research conducted in this study is field research. Field research is research carried out in real-life settings. The field research in this study specifically refers to research conducted at SMA Negeri 1 Purbolinggo, focusing on the implementation of the Merdeka Curriculum in history learning. The results of the research on the implementation of the Merdeka Curriculum in history learning at SMA Negeri 1 Purbolinggo include planning, execution, evaluation, and challenges in the learning process. The planning phase involves training, guidance, in-house training workshops (IHT), and the preparation of learning tools. The implementation of the Merdeka Curriculum in history learning includes introductory activities, main activities, and closing, with teachers conducting lessons based on the prepared learning tools. The evaluation covers both summative and formative assessments, and evaluations are conducted comprehensively for every school program. The challenges in history learning at SMA Negeri 1 Purbolinggo include low student motivation and a lack of adequate technological facilities, such as LCDs and projectors.